1979
DOI: 10.1002/j.1879-3479.1979.tb00453.x
|View full text |Cite
|
Sign up to set email alerts
|

The Place of Sling Operations in Treating Genital Prolapse in Young Women

Abstract: A review of 260 cases of genital prolapse in women less than 35 years of age is presented. Thirty‐six percent of the women were less than 25 years old, and 73.5% were less than 30 years. Until 1965, a total of 85 patients had undergone either Manchester operations or simple colporrhaphies after a conventional method of treatment. Since then, a different surgical approach was elected, and patients were divided into four groups according to the severity of their conditions and the types of operation required. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…In another study conducted by Chaudhari S.K. et al, [15] fertility was not affected in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…In another study conducted by Chaudhari S.K. et al, [15] fertility was not affected in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, there was a higher rate of spontaneous abortion (SAB) or preterm labor (combined 4/7) and the majority of patients required cesarean section for delivery (2/3). 11 In another series of 82 patients, five patients desired future fertility after Manchester procedure; three conceived and two of the three carried pregnancies to full term. Furthermore, in patients not desiring future fertility, there were three unplanned pregnancies, all of which went to term, and only one cesarean section is reported.…”
Section: Discussionmentioning
confidence: 98%
“…8,9 A review of pregnancies following Manchester procedure revealed reduced fertility in the range of 21-33%. 10, 11 Fisher reviewed of 30,000 obstetrical cases and identified 7 women who underwent the Manchester Procedure between the ages of 23 and 38. Prior to the operation these women had a total of 21 full term deliveries, with one spontaneous abortion and one incident of pre-term labor.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-six percent of the women were less than 25 years old, and 73.5% were less than 30 years [3] . Even in neonates, genital prolapse may be seen, as a result of congenital spinal defects [4] .…”
Section: Discussionmentioning
confidence: 99%
“…In 1978, Chaudhuri [3] presented 260 cases of genital prolapse in women less than 35 years of age. Thirty-six percent of the women were less than 25 years old, and 73.5% were less than 30 years [3] .…”
Section: Discussionmentioning
confidence: 99%